Community Thought about The Existence of Jiwa Temple - Didin Komarudin (el Harakah: Jurnal Budaya Islam, 2019)
Many relics from the results of historical civilization are evidence of the existence of life in ancient times. Segaran village has Jiwa temple of the Tarumanagara royal civilization which is still Hindu-Buddhist. This article is to find out the existence of this temple to the surrounding community and the Muslim community around it and interpret it as a result of the relics of the Hindu-Buddhist kingdom. The study used a descriptive method by describing and systematically explaining the fact of the existence of the temple and the meaning of the views of the Muslim community around it. The finding shows that the existence of this temple has a significant influence on the surrounding community, especially in the economic field, while the meanings and views of the Muslim community around it are different, some consider it sacred and vice versa. Jiwa temple has an enormous influence on the lives of the surrounding communities in the form of economic factors in particular, social and religious. The local community interpreted and also viewed the temple as a cultural monument, a historical heritage that must be protected and preserved.  Banyak peninggalan dari hasil peradaban historis menjadi bukti keberadaan kehidupan di zaman kuno. Desa Segaran memiliki Jiwa temple dari peradaban kerajaan Tarumanagara yang masih beragama Hindu-Budha. Artikel ini mengulas keberadaan Jiwa temple bagi masyarakat dan komunitas Muslim di sekitarnya dan menafsirkannya sebagai hasil peninggalan kerajaan Hindu-Budha. Penelitian ini menggunakan metode deskriptif dengan menggambarkan dan secara sistematis menjelaskan fakta keberadaan candi dan makna pandangan komunitas Muslim di sekitarnya. Temuan menunjukkan bahwa keberadaan candi ini memiliki pengaruh besar pada masyarakat sekitarnya, terutama di bidang ekonomi, sementara makna dan pandangan komunitas Muslim di sekitarnya berbeda, beberapa menganggapnya suci dan sebaliknya. Jiwa temple memiliki pengaruh besar pada kehidupan masyarakat dalam bentuk faktor ekonomi khususnya, sosial dan keagamaan. Masyarakat setempat menafsirkan dan juga memandang candi sebagai monumen budaya, warisan sejarah yang harus dilindungi dan dilestarikan.